Abnormal uterine bleeding in a woman with caesarean scar defect (isthmocele): a case report - S., Abhishek; Shreevijay, B.; M., Sona; Kulkarni, Shashank (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2022)
The caesarean scar defect generally is described as a triangular or circular sonographically anechoic area in the myometrium of the anterior lower uterine segment or cervix at the site of a previous caesarean section. Caesarean section is one of the most commonly performed surgeries and the trend is increasing in the recent years. One long-term complication of caesarean delivery which is not often discussed is the presence of a defect within the uterine scar that is directly associated with a type of abnormal uterine bleeding (AUB) referred to as postmenstrual bleeding. In addition to AUB, presented as pelvic pain, dyspareunia, dysmenorrhea, unexplained infertility. Caesarean scar defect is one such cause of AUB which is overlooked as the history of caesarean section will be many years ago. One such case of woman presenting with abnormal uterine bleeding and pain in abdomen with caesarean defect who was managed in our tertiary care centre reported here.